1988
DOI: 10.1177/070674378803300616
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Aspects of Ultrasound Imaging during Pregnancy

Abstract: The psychological impact of ultrasound examination on expectant parents is assessed through direct observation, interviews and the administration of a questionnaire to a large group of parents. The examination was a positive and reassuring experience for most parents. Among a wide array of variables that could account for the effects of the exam, the results were the most important. Women viewing their first ultrasound, specially primiparae were more moved. The results did not confirm that there is a traumatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0
15

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 3 publications
2
48
0
15
Order By: Relevance
“…That sort of statement also showed what great importance the routine ultrasound examination had to the fathers, and what an overwhelming experience it had been for them. Villeneuve et al (1988) 22 also found, when interviewing fathers, that their feelings and reactions were just as strong as those of the mothers. This research group also discovered that mothers felt it very important that their partners were present during the examination, which might have increased the intensity of their excitement and grade of bonding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That sort of statement also showed what great importance the routine ultrasound examination had to the fathers, and what an overwhelming experience it had been for them. Villeneuve et al (1988) 22 also found, when interviewing fathers, that their feelings and reactions were just as strong as those of the mothers. This research group also discovered that mothers felt it very important that their partners were present during the examination, which might have increased the intensity of their excitement and grade of bonding.…”
Section: Discussionmentioning
confidence: 99%
“…The parents linked the impression of good treatment to the information given. Villeneuve et al (1988) found during routine screening's infancy, a poor understanding of the image amongst 60% of 154 Canadian women. Some women in their study were not shown the image at all, which caused disappointment.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Diagnoses resulting from prenatal US include multiple gestation, congenital fetal abnormalities, fetal growth problems and amniotic fluid or placental abnormalities. Study of US as a perinatal diagnostic tool has focused on whether US improves perinatal outcomes, [3][4][5][6] the psychological effect on women and men of such an examination, [7][8][9] perception and receipt of information, [10][11][12][13][14] and the experiences of staff who perform US examinations. 15,16 A 1998 Cochrane review of routine US 17 focused only on physical outcomes, as did a later work.…”
Section: Introductionmentioning
confidence: 99%
“…Os resultados revelaram que tais gestantes manifestaram uma preferência defi nida por um dos sexos, mesmo sendo primíparas, o que não corrobora as ideias apresentadas por alguns autores (Villeneuve, Laroche, Lippman, & Marrache, 1988;Wu & Eichmann, 1988). Eles referem que, em geral, as mães primíparas não costumam ter ou expressar uma predileção sobre o sexo do bebê, justamente por ainda não terem fi lhos.…”
Section: Discussionunclassified